Systematic Development of Self-Nanoemulsifying Liquisolid Tablets to Improve the Dissolution and Oral Bioavailability of an Oily Drug, Vitamin K1 - Yongtao Tong; Yuli Wang; Meiyan Yang; Jiahui Yang; Lu Chen; Xiaoyang Chu; Chunhong Gao; Qian Jin; Wei Gong; Chunsheng Gao (MDPI AG, 2018)
The purpose of this study is to improve the dissolution and oral bioavailability of an oily drug, vitamin K1 (VK1) by combination of self-nanoemulsifying and liquisolid technologies. The optimal liquid self-nanoemulsifying drug delivery systems (SNEDDS) formulation including VK1 (oil), mixture of soybean lecithin and glycocholic acid (surfactant) and Transcutol HP (cosurfactant) was obtained according to ternary phase diagrams and a central composite design. Based on compatibility, adsorption capacity and dissolution profile, liquid SNEDDS was then solidified on Fujicalin® to form solid SNEDDS by liquisolid technology and compressed directly with excipients into self-nanoemulsifying liquisolid (SNE-L) tablets. Uniform nano-emulsion suspension was formed rapidly when the SNE-L tablets disintegrated in dissolution media and higher drug dissolution was observed compared with the conventional tablets. The results of pharmacokinetic study in beagle dogs showed that the mean Cmax and the area under the curve of SNE-L tablets were remarkably higher than those of conventional tablets, which were consistent with the results of the in vitro dissolution. The relative bioavailability of SNE-L tablets and conventional tablets was approximately 200%. In conclusion, this combination method showed promise to improve the dissolution and oral bioavailability of oily drug vitamin K1.